(untitled) (Economics and region, 2022)
This article is devoted to the qualitative analysis of the positioning of Austrian oil & gas producer OMV in terms of market competition, the industry as well as ESG standards. We researched the oil & gas industry to understand the positioning of OMV and compared it to competitors. Moreover, we analysed ESG-related topics since sustainability has become a relevant topic recently, especially in Europe, so companies must comply with environmental, social, and governance regulations. Driver to transform OMV to an integrated petrochemical company is developing in the long run due to worldwide sustainability trends. There is promising growth for the petrochemical industry as well and OMV is moving forward with expanding its sustainability portfolio as well as launching projects and integrations relating to ESG topics.